2017
DOI: 10.1155/2017/9858923
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncological Outcomes for Young Men Undergoing Radical Prostatectomy for Localized Prostate Cancer

Abstract: Aim. The aim of this study was to describe PCa characteristics and long-term outcomes in young men aged ≤55 years after radical prostatectomy (RP) and to compare them with older men cohort. Methods. Among 2,200 patients who underwent RP for clinically localized PCa at our centre between 2001 and 2015, 277 (10.3%) men aged ≤55 years were identified. All preoperative and pathological parameters were compared between groups. Biochemical progression free survival (BPFS) and disease progression free survival (DPFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This result is consistent with the literature (Ross et al, 2016). Previous research has identified that marital status and relationship satisfaction are both protective factors of mortality and poor quality of life, including certain aspects of mental health among PCa survivors (Bill-Axelson et al, 2013;Christie & Sharpley, 2014;Donovan et al, 2016;Eton & Lepore, 2002;Isbarn et al, 2010;Milonas et al, 2017;Occhipinto et al, 2019;Ross et al, 2016). To our knowledge, although important, there are no previous studies that have controlled for the presence or absence of current prescribed medication for anxiety, depression, or both, in studies examining mental health outcomes in this population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with the literature (Ross et al, 2016). Previous research has identified that marital status and relationship satisfaction are both protective factors of mortality and poor quality of life, including certain aspects of mental health among PCa survivors (Bill-Axelson et al, 2013;Christie & Sharpley, 2014;Donovan et al, 2016;Eton & Lepore, 2002;Isbarn et al, 2010;Milonas et al, 2017;Occhipinto et al, 2019;Ross et al, 2016). To our knowledge, although important, there are no previous studies that have controlled for the presence or absence of current prescribed medication for anxiety, depression, or both, in studies examining mental health outcomes in this population.…”
Section: Discussionsupporting
confidence: 91%
“…Prostate cancer (PCa) is the most commonly diagnosed cancer among Canadian men and radical prostatectomy (RP) remains the gold standard treatment for localized disease in men with PCa ( Canadian Cancer Statistics Advisory Committee, 2019 ; Isbarn et al, 2010 ; Milonas et al, 2017 ). Given the high survival rates among patients undergoing RP (10-year PCa-specific mortality-free survival rates exceed 90%), a greater emphasis has been placed on understanding survivorship issues such as incontinence and mental distress ( Donovan et al, 2016 ; Eton & Lepore, 2002 ).…”
mentioning
confidence: 99%
“…patients were characterized by the poorest prognosis [ 61 ]. There are also some new evidences that males aged under 50 years had similar pathological tumor characteristic, histological grade, disease stage, PSA level and biochemical free survival compared to the older population [ 62 , 63 ]. Our finding shows fundamental molecular differences between prostate cancers form young and old patients.…”
Section: Discussionmentioning
confidence: 99%
“…Classically described as a disease of the elderly, PC is steadily rising in incidence among younger men: approximately 43.6% of new cases are expected to occur in men aged <65 years in 2018 alone . Rates of radical prostatectomy have also increased, particularly for men with high‐risk disease . Consequently, more patients will likely require postprostatectomy RT given biochemical/local control and possibly survival benefits in the adjuvant and salvage settings .…”
Section: Discussionmentioning
confidence: 99%
“…31 Rates of radical prostatectomy have also increased, particularly for men with high-risk disease. 32,33 Consequently, more patients will likely require postprostatectomy RT given biochemical/ local control and possibly survival benefits in the adjuvant [34][35][36][37][38][39] and salvage settings. [40][41][42] Emerging technological developments in PBT, such as smaller footprint beamdelivery systems, will result in significant cost reduction and broader financial accessibility in the future.…”
Section: Radiobiological Insights and Long-term Outcomesmentioning
confidence: 99%